Human Resource Management Strategy in Facing the Educational Transformation of the Society Era 5.0 in Islamic Boarding Schools - Anton Respati Pamungkas; Agus Nugroho; Hartawan Hartawan; Sachin Gupta (Journal of Nonformal Education, 2025)
Background - Islamic boarding schools as one of the educational institutions based on Islamic values have a strategic role in the development of human resources in Indonesia. However, in the era of Society 5.0—which is characterized by the convergence of digital technology and human life—Islamic boarding schools face great challenges in adapting their learning systems and approaches. This condition requires adaptive and innovative human resource management (HR) in order to be able to respond to the demands of the times. Purpose - This research aims to analyze the role of human resource management in facing the dynamics and challenges of the world of education in the era of Society 5.0, with a case study on the Al-Furqan Islamic Boarding School Banjarmasin. Method/approach - This study uses a qualitative approach with data collection methods through observation, in-depth interviews, and documentation studies. Findings - The results of the study show that human resource management in this Islamic boarding school is carried out through a selective recruitment process, continuous training, teacher competency development, a structured performance evaluation system, and motivational awarding. Islamic boarding schools also integrate technology in learning and organize digital literacy training for educators in response to the challenges of the Society 5.0 era. Conclusions - The conclusion of this study states that responsive and strategic human resource management is the main key in maintaining the sustainability of the quality of education in Islamic boarding schools. Novelty/Originality/Value - The novelty of this study lies in the identification of the specific role of human resource management in the context of traditional educational institutions (Islamic boarding schools) that are undergoing digital transformation in the era of Society 5.0—a perspective that is still rarely explored in academic studies.